Necesidades de tratamiento en dentición primaria en niños de uno a cinco años con caries dental no tratada en una comunidad de bajos ingresos. Moravia, Medellín, 2006 (2009)
ABSTRACT: The purpose was to establish non treated dental caries prevalence and treatment needs in 1 to 5 year old children living in a low-income neighborhood in Medellin. Methods: a cross-sectional study was performed in 162 children. A calibrated (Kappa 0.73) examiner assessed dental status according to Pitts & Fyffe criteria. Based on caries lesions advance (D1-D4), treatment needs were defined, according to current guidelines promoting a preventive and less invasive approach. The proportion of non-treated dental caries was estimated, as well as the average and standard deviation of teeth per child requiring different treatment categories. Results: from the total 162 children, 77.8% had non treated dental caries, each child having 5.8 ± 4.1 teeth needing some kind of treatment. From all dental caries lesions, 47% correspond to initial enamel lesions or small cavity confined to enamel (D1 - D2), potentially controlled by preventive treatment, and 53% compromise dentin and pulp (D3 - D4). Treatment needs increased with age. Conclusions: high prevalence of Early Childhood Caries and non-treated dental caries lesions reflects cumulated treatment needs in this low income population and support a relationship between dental caries, inequalities and living conditions, limiting access to effective and opportune dental care.